Complementos a la descripción de Tityus dedoslargos (Scorpiones: Buthidae) - de Armas, Luis F (2002)
The female of the Costarican scorpion Tityus dedoslargos Francke and Stockwell, 1987 is described for the first time and new data on its morphological variation and natural history are given. The female differs from the male mainly in having an enlarged basal median lamellae on the pectines, and lacking modified pedipalps. The species type localiy is relocated. This species is recorded from only two Costarican provinces: San Jose and Puntarenas.